Radiation to all macroscopic sites of tumor permits greater systemic antitumor response to in situ vaccination - Zachary S Morris; Paul M Sondel; Amy K Erbe; Alexander L Rakhmilevich; Amber M Bates; Peter M Carlson; Alexander A Pieper; Ravi B Patel; Jen Birstler; Joseph Grudzinski; Reinier Hernandez; Bryan P Bednarz; et al. (Journal for ImmunoTherapy of Cancer)
Background The antitumor effects of external beam radiation therapy (EBRT) are mediated, in part, by an immune response. We have reported that a single fraction of 12 Gy EBRT combined with intratumoral anti-GD2 hu14.18-IL2 immunocytokine (IC) generates an effective in situ vaccine (ISV) against GD2-positive murine tumors. This ISV is effective in eradicating single tumors with sustained immune memory; however, it does not generate an adequate abscopal response against macroscopic distant tumors. Given the immune-stimulatory capacity of radiation therapy (RT), we hypothesized that delivering RT to all sites of disease would augment systemic antitumor responses to ISV.Methods We used a syngeneic B78 murine melanoma model consisting of a ‘primary’ flank tumor and a contralateral smaller ‘secondary’ flank tumor, treated with 12 Gy EBRT and intratumoral IC immunotherapy to the primary and additional EBRT to the secondary tumor. As a means of delivering RT to all sites of disease, both known and occult, we also used a novel alkylphosphocholine analog, NM600, conjugated to 90Y as a targeted radionuclide therapy (TRT). Tumor growth, overall survival, and cause of death were measured. Flow cytometry was used to evaluate immune population changes in both tumors.Results Abscopal effects of local ISV were amplified by delivering as little as 2–6 Gy of EBRT to the secondary tumor. When the primary tumor ISV regimen was delivered in mice receiving 12 Gy EBRT to the secondary tumor, we observed improved overall survival and more disease-free mice with immune memory compared with either ISV or 12 Gy EBRT alone. Similarly, TRT combined with ISV resulted in improved overall survival and a trend towards reduced tumor growth rates when compared with either treatment alone. Using flow cytometry, we identified an influx of CD8+ T cells with a less exhausted phenotype in both the ISV-targeted primary and the distant secondary tumor following the combination of secondary tumor EBRT or TRT with primary tumor ISV.Conclusions We report a novel use for low-dose RT, not as a direct antitumor modality but as an immunomodulator capable of driving and expanding antitumor immunity against metastatic tumor sites following ISV.